A review of potential applications of Tensor Decompositions to Electromagnetics and energy works - Mageed I.A.; Yilmaz M.; Zhang Q.; Celikel R.; Sidhu M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Tensors; Uncertainty analysis; Canonical polyadic; Electromagnetic analysis; Electromagnetic solvers; Electromagnetics; Energy; Energy work; Smart grid; Surrogate modeling; Tensor decomposition; Uncertainty quantifications; Smart power grids